Optimisation of envelope insulation for the retrofit of an educational building - N.M.M. Ramos (2011)
This paper presents ongoing work for the definition of an optimal design strategy for retrofitting educational buildings. The term "optimal design" refers to the selection of different retrofitting solutions to ensure an energy efficient building that can be developed which will not compromise hygrothermal comfort, indoor air quality, health and durability. In this paper, a selection model of thermal insulation thickness of envelope elements is developed, aiming the control of surface condensation and upgrade of hygrothermal comfort. The mathematical formulation of this model leads to a nonlinear program with linear objective function. The software Gmas/Minos was chosen to solve the optimization problem and to develop a calculation program to solve this specific application. The software Energy-Plus developed by the US Department of Energy was used to simulate hygrothennal performance of the building, providing results for a comparison with the developed simulation tool. The paper presents an example of an optimal design problem for a specific classroom of a retrofit educational building.